Urban insiders versus rural outsiders: complementarity or competition in China's urban labour market? - Knight, J; Yueh, L (University of Oxford, 2004)
In China urban residents have traditionally been protected against labour market competition from rural-urban migrants. Over the period of urban economic reform, rural-urban migration was allowed to increase in order to fill the employment gap as growth of labour demand outstripped that of the resident labour force in urban areas. However, as reforms gained pace and controls were lifted, it is plausible that migrants and urban residents increasingly competed. The paper examines whether the relationship is one of complementarity in a still segmented labour market or of substitutability in an increasingly competitive labour market. It uses attitudinal responses from two urban surveys and a panel data set covering the 30 provinces over the period 1994-2000. We obtain very different results from cross-section, random effects and fixed effects panel estimates, raising interesting methodological issues. The findings are consistent with the presence of continued labour market segmentation but suggest also that competition between the two groups may be increasing.